Hydrated Seal Lip for Live Center in Machine Tools - Akiyama, Tetsuya; Yoshioka, Yuki; Honda, Takuro; Nakashima, Yuta; Nakanishi, Yoshitaka (Frontiers in Mechanical Engineering, 2018)
When performing a cutting operation, a water-soluble cutting fluid may be used for cooling. Labyrinth and oil seals are commonly used in the rotating centers of machine tools to prevent the cutting fluid and dust from entering the inner parts. However, these seals do not demonstrate adequate functionality in a water-based environment. Therefore, a new rotary shaft seal was devised to separate the water-soluble cutting fluid from interacting with air. The rotary shaft seal was made from polyvinyl formal (PVF). Because PVF is a hydrophilic material, it is expected to provide suitable functionality as a seal in a water-based environment. Performance evaluations of PVF and oil seals were experimentally obtained and compared from the point of view of frictional torque, water-soluble cutting fluid leakage volume, and service life as a seal.